Diagnostic Accuracy of Sonosalpingography for Assessing Tubal Patency in Women with Infertility Taking Laparoscopy as Gold Standard - Naheed Khan, Kanwal Rehana, Sidra Saeed, Hina Gul, Kalsoom Nawab, Irsa Shoaib (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Infertility is defined as the failure to conceive after 1 year of unprotected sexual intercourse in women less than 35 years of age and 6 months in women older than 35 years [1, 2]. It affects 10 to 15 % of the couples [1]. Abnormalities of fallopian tubes account for 35 to 40 % of the cases of infertility [3]. Sonosalpingography is a non-invasive, safe and cost- effective diagnostic technique which provides reliable diagnosis of tubal patency [4]. Objective: To evaluate the diagnostic validity of Sonosalpingography as a tubal patency test in infertile women using laparoscopy as gold standard. Methodology: This study was carried out at the Radiology Departments of Khyber Teaching Hospital and Kuwait Teaching Hospital in Peshawar. We used the WHO method for sample size by taking the prevalence of tuboperitoneal factors as 30%, sensitivity 72.9%, specificity 81.22%, margin of error 12%, and 95% confidence interval. It was a cross-sectional study that lasted for 6 months and assessed a total of 178 patients. Additionally, a non-probability, sequential sampling strategy was utilized to acquire the sample. Results: Our patients aged between 18-45 years, out of which 30% of the participants aged 18 to 25years, 55% were between 26 and 35years, and 15% were between 36 and 45years. Standard deviation was 1.26, with a mean age of 27. The data collected from both the diagnostic tests was analyzed, diagnostic accuracy of Sonosalpingography was calculated as a sensitivity of 81%, specificity of 76%, positive predictive value of 90%, negative predictive value of 60%, and diagnostic accuracy of 79%. Conclusion: According to the results of our study, sonosalpingography is a very helpful supplemental diagnostic tool for evaluating tubal disease in patients with infertility, though direct laparoscopic assessment is the gold standard. Sonosalpingography and laparoscopy can be used to evaluate patients with secondary infertility. This spares the patient from being exposed to radiations and the discomfort of contrast administration in HSG. Keywords: Diagnostic Accuracy, Sonosalpingography, Tubal Patency, Infertility, Laparoscopy